Writing With a Word Processor - Zinsser, William (Mexico City Harper and Row, Publishers, 1983)
Writing With a Word Processor is a manual for beginners that describes clearly and simply how to use the new technology. But it is also one writers story. William Zinsser takes the reader along on a highly personal journey, writing with warmth and humor about his anxieties and fears, his setbacks and triumphs. His book is both an information guide and an encouraging companion.
Keywords: Science